Carbodiimides as energy materials: which directions for a reasonable future?. Issue 32 (20th July 2018) - Sougrati, Moulay T.; Arayamparambil, Jeethu J.; Liu, Xiaohui; Mann, Markus; Slabon, Adam; Stievano, Lorenzo; Dronskowski, Richard
Abstract : Transition-metal carbodiimides have emerged as energy materials, both as anodes in rechargeable batteries and as catalysts in photochemical water oxidation. Abstract : A little less than a decade after their quantum-chemical prediction and eventual synthesis, solid-state transition-metal carbodiimides and closely related compounds have somewhat unexpectedly emerged as energy materials. In these carbodiimides, the O 2− oxide dianion has been replaced by the complex NCN 2− dianion, and the outstanding properties of such materials are likely related to their metastability and their higher amount of covalency compared to related oxides. When used as anode materials in rechargeable Li- and Na-ion batteries, one finds a conversion reaction, and further improving their performance will likely involve studying the redox behavior of NCN 2−, the synthesis of novel ternary carbodiimides, in particular those with redox-active transition metals, and controlling their morphology. At present, such materials serve as catalysts in photochemical water oxidation, where they outperform their oxide cousins.